Quantitative study of spatiotemporal changes in ecology to monitor land degradation in Alborz Province. - N. Mostafavi; Gh. Zehtabian; H. Azarnivand; H. Keshtkar; Hassan Khosravi (Desert)
The expansion of human activities has caused widespread disturbances in ecosystems worldwide, necessitating the development of effective tools to monitor and quantify these changes. Remote sensing stands as a powerful tool for monitoring and quantifying ecological changes over time and space. In this study, a remote sensing-based ecological index (RSEI) was used to investigate land degradation and desertification in Alborz province during the period 2000-2020. After examining land use changes, the trend of RSEI outputs was evaluated using the Mann-Kendall test and Theil-Sen estimator. The examination of land use changes during the period 2000-2020 showed that barren lands, rangelands, shrublands and forests decreased by 2.30%, 6.25%, 1.53%, and 0.18%, respectively, while crop lands, built-up lands, and dam increased by 8.23%, 1.85%, and 0.18%, respectively. The analysis of the trend of changes in the RSEI using the Mann-Kendall test showed that the changes in 16.27% of Alborz province was decreasing, of which about 0.5% was statistically significant. This decreasing trend was also shown by the Theil-Sen estimator in 13% of this region. The results of this study using the Mann-Kendall test also showed that the RSEI values increased in 80.73% of the study area, of which about 4% increased significantly. The analysis of changes in this index using the Theil-Sen estimator showed that this index increased in 87% of this region. This study suggests that the RSEI approach performs effectively in quantifying and detecting ecological changes and, as a result, land degradation at various scales.